Curbing boredom in online teaching: Effects of an autonomy-oriented intervention with EAP students - Rezaee, Abbas Ali; Seyri, Haniye (Frontiers in Psychology, 2022)
Despite the growing body of research on boredom and its causes in face-to-face classes, little is known about how pedagogical interventions can mitigate this negative emotion. The purpose of this study was to examine boredom experienced by EAP students in online classes and investigate the effects of an autonomy-oriented intervention program on students' boredom. The Boredom Scale developed by Kruk and Zawodniak (2017) was administered to 84 students before and after the autonomy-oriented intervention. By designing and implementing autonomy-oriented intervention based on the autonomy enhancement model proposed by Benson (2011), positive results were obtained with reduced levels of boredom. The results of the paired sample t-test showed significant changes in the boredom experienced by students after the intervention and it reduced to a noticeable extent. In addition, the qualitative results contributed to our understanding of the learners' experiences throughout the intervention. We conclude the study with implications for EAP instructors to employ different pedagogical interventions to mitigate negative emotions in online EAP classes.